2012
DOI: 10.1186/1475-2875-11-280
|View full text |Cite
|
Sign up to set email alerts
|

Primaquine radical cure of Plasmodium vivax: a critical review of the literature

Abstract: BackgroundPrimaquine has been the only widely available hypnozoitocidal anti-malarial drug for half a century. Despite this its clinical efficacy is poorly characterized resulting in a lack of consensus over the optimal regimen for the radical cure of Plasmodium vivax.MethodsPublished studies since 1950 of the use of primaquine regimens for preventing P. vivax relapse were reviewed. Data were extracted systematically from available papers. Primaquine regimens were categorized according to the total dose admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
162
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(167 citation statements)
references
References 31 publications
(34 reference statements)
2
162
0
3
Order By: Relevance
“…In Cochrane Infectious Diseases Group, we found the same as in Cochrane Library. In PubMed we found review articles and meta-analysis ones; in both cases, many references were obtained 5,6,[13][14][15] . The search in Scholar Google yielded 94 results; the titles in the writings were compared to the ones obtained in all other sources, but it resulted in no new reference which would meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Cochrane Infectious Diseases Group, we found the same as in Cochrane Library. In PubMed we found review articles and meta-analysis ones; in both cases, many references were obtained 5,6,[13][14][15] . The search in Scholar Google yielded 94 results; the titles in the writings were compared to the ones obtained in all other sources, but it resulted in no new reference which would meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Because, regarding the review by Cochrane, we found 23 studies instead of 9; we analyzed 5 treatment schemes instead of 3 (0: zero mg of PQ; 75-5: 75 mg of PQ distributed into 5 days; 210-14: 210 mg of PQ distributed into 14 days); we worked with 6,350 patients instead of 3,423. In relation to the meta-analysis made by John et al 15 , it included segments of < 30 days (that measure the response of the acute attack); it included 7 studies without schizonticide, the TD categories used include one which contains the standard TD used in the standard procedure (14 days) or in 7 days, along with higher TD such as 315-14 (315 mg of PQ distributed into 14 days), 420-14 (420 mg of PQ distributed into 14 days), etc, and it does not discriminate the results among these values; because it includes Prospective and Retrospective studies; because it includes many studies without control group, it is to say Descriptive and solo CCT studies, without differentiating the recurrences in relation to the kind of study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 In addition, our data also indicate that untreated, asymptomatic P. vivax infections can be of very short duration (2-4 weeks). Together these observations highlight that anti-hypnozoite treatment efficacy studies need long-term follow-up with intensive and active monitoring for asymptomatic infections (ideally by PCR given the low densities) 20 ; otherwise such studies may overestimate the efficacy of primaquine and novel anti-liverstage drugs such as tafenoquine.…”
mentioning
confidence: 99%